Odpowiedzi

2010-03-14T22:35:18+01:00
A)(y+4)(1+3)-(-1+4)(x+3)=0
(y+4)*4-3(x+3)=0
4y+16-3x-9=0
4y+7-3x=0
4y=(-7+3x)/4
y=-7/4+3/4x
b)(y+1)(-2-1)-(1+1)(x-1)=0
(y+1)*(-3)-2(x-1)=0
-3y-3-2x+2=0
-3y-2x-1=0
-3y=(2x+1)/(-3)
y=-2/3x-1/3

współrzędne punktu D (punktu leżącego w połowie prostej BC)

x=(1-2)/2=-1/2
y=(-1+1)/2=0

współrzędne punktu D=(-1/2 i 0)

y=3/2x+b
0=3/2*(-1/2)+b
0=-3/4+b
3/4=b

równanie symetralnej odcinka BC to: y=3/2x+3/4

c)A=(-3,-4) C=(-2,1)

|AC|=pierwiastek[(-2+3)^2+(1+4)^2]
|AC|=pierwiastek[1^2+5^2]
|AC|=pierwiastek[1+25]
|AC|=pierwiastek[26]
|AC|=pierwiastek z 26